Web-based database application for supporting cancer research - Gan, Soon Ann (2008)
Due to the advancement of medicine and the move towards evidence-based medicine practices, more and more physicians are interested in collecting clinical data for research purposes. An efficient way to collect and analyze data involves the use of information technology. However, one of the main challenges faced when trying to build a system that fulfills the needs of collecting clinical data is the dynamics of clinical parameters. As new types of tests, drugs or surgical treatments are being introduced, the values of clinical parameters that need to be captured also change accordingly.